Factors Associated with Tuberculosis Treatment Success Among Human Immunodeficiency Virus - Tuberkulosis (HIV-TB) in H. Adam Malik General Hospital, Medan - Anna Yusria; Ning Rintiswati; Sumardi Sumardi (Pusat Kedokteran Tropis, 2017)
Introduction: Co-infection of TB/HIV is currently a serious health threat to the world population. Efforts to control tuberculosis and HIV programs still facing obstacles, especially if the two diseases allied, it will be more difficult and challenging for both prevention program. Both TB and HIV have higher burden disease and need to be cope urgently. Adequate treatment of TB in co-infected patients can reduce the high morbidity and mortality of patients, prevent treatment failure and improve the success rate.Objectives: Determine the proportion of successful treatment of TB among HIV-TB patients in H. Adam Malik General Hospital between 2011-2013 and identified the factors that influenced the success of their TB treatment.Methods: A case control study design using medical records of HIV-TB patients in VCT polyclinic of H. Adam Malik General Hospital from 2011-2013.Results: The average success rate of TB treatment among HIV-TB patients in H. Adam Malik General Hospital was 68.56%. Male, age ≤40 years, pulmonary TB, CD4 count <200, anemia, HIV stage 3 and adherence to TB treatment dominated this research, (60,82%, 76,29%, 71,13%, 74,23%, 60,82%, 55,15% and 53,09% respectively). Gender (aOR 3.87 95% CI: 1.21 - 18.31), CD4 101-200 (aOR 5.06 95% CI: 1.06 - 24.04), CD4> 200 (aOR 15, 80 95% CI: 3.18 - 78.64), status of anemia (aOR 2.00 95% CI: 1.22 - 3.26) and adherence to TB treatment (aOR 6.16 95% CI: 2.07 - 18.31) were statistically significant in multivariate analysis. Other factors such as age, classification of TB disease and HIV stage were not significant (p values> 0.05). Conclusion: Female, CD4 cell counts 101-200, CD4 count> 200, status of anemia and adherence to TB treatment determined the successful of TB treatment among HIV-TB patients. Implementation of TB/HIV collaborative program and DOTS strategy in TB treatment increases the success rate of TB treatment among HIV-TB patients at H. Adam Malik General Hospital.Keyword: success, tuberculosis treatment, HIV-TB INTISARIPendahuluan: Ko-infeksi TB/HIV saat ini menjadi ancaman kesehatan serius bagi penduduk dunia. Upaya penanggulangan program TB maupun HIV selama ini masih menghadapi kendala apalagi jika kedua penyakit tersebut bersekutu akan lebih menyulitkan dan menjadi tantangan bagi penanggulangan kedua program. Baik TB maupun HIV, keduanya mempunyai burden disease yang cukup tinggi untuk segera ditangani. Pengobatan TB yang adekuat pada pasien koinfeksi dapat menekan tingginya angka morbiditas dan mortalitas pasien, mencegah kegagalan terapi serta meningkatkan angka keberhasilan.Tujuan: Mengetahui proporsi keberhasilan pengobatan TB pada penderita HIV di RSUP H. Adam Malik Medan tahun 2011-2013 serta mengidentifikasi faktor-faktor yang mempengaruhi keberhasilan pengobatan TB-nya.Metode: Desain penelitian yang digunakan adalah case control, menggunakan data sekunder Poliklinik VCT Pusyansus RSUP H. Adam Malik Medan 2011-2013.Hasil: Rata-rata keberhasilan pengobatan TB pada penderita HIV di RSUP H. Adam Malik Medan tahun 2011-2013 sebesar 68,56%. Jenis kelamin laki-laki, umur ≤40 tahun, lesi TB di paru, jumlah CD4 <200, status anemia, stadium 3 HIV dan keteraturan pengobatan OAT mendominasi penelitian ini, masing-masing sebesar 60,82%, 76,29%, 71,13%, 74,23%, 60,82%, 55,15% dan 53,09%. Variabel jenis kelamin (aOR 3,87 95%CI: 1,21 - 18,31), jumlah CD4 101-200 (aOR 5,06 95%CI: 1,06 - 24,04), CD4 >200 (aOR 15,80 95%CI: 3,18 - 78,64), tidak anemia (aOR 2,00 95%CI: 1,22 - 3,26) dan keteraturan pengobatan TB (aOR 6,16 95%CI: 2,07 - 18,31) berhubungan signifikan dalam analisis multivariat. Faktor lain yaitu umur, klasifikasi penyakit TB dan stadium HIV tidak bermakna (nilai p>0,05).Simpulan: Jenis kelamin perempuan, jumlah CD4 101-200, jumlah CD4 >200, tidak anemia dan teratur menjalani pengobatan OAT menentukan keberhasilan pengobatan TB pada penderita HIV-TB. Implementasi program kolaborasi TB/HIV dan penerapan strategi pengobatan TB dengan DOTS meningkatkan angka keberhasilan pengobatan TB di RSUP H. Adam Malik Medan.Kata kunci: keberhasilan, pengobatan tuberkulosis, HIV-TB